Kloning dan Analisis Bioinformatika Gen MSP1 Plasmodium falciparum Isolat Kota Jayapura - Arsyam Mawardi; Leonardo E. Aisoi; Paula N. Lefaan (Jurusan Biologi FMIPA Universitas Cenderawasih, 2018)
Cloning gene involves the construction of a recombinant plasmid that inserted in a competent cell. On the other hand, genetic engineering requires bioinformatic analysis to be converted into tabulation and data interpretation. The study, titled